2012
DOI: 10.5194/angeo-30-389-2012
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting "Narrow Bipolar Event" intracloud lightning using the FORTE satellite

Abstract: Abstract. The lightning stroke called a "Narrow Bipolar Event", or NBE, is an intracloud discharge responsible for significant charge redistribution. The NBE occurs within 10-20 µs, and some associated process emits irregular bursts of intense radio noise, fading at shorter timescales, sporadically during the charge transfer. In previous reports, the NBE has been inferred to be quite different from other forms of lightning strokes, in two ways: First, the NBE has been inferred to be relatively dark (non-lumino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Table 4 identifies the six events and gives the time difference (median HUMR minus PDD), which is negative because the HUMR energy-weighted center time is earlier than the PDD trigger time. It has been observed in the past that dominant strong TIPPs, corresponding to the most restrictive category in produce enough light to trigger PDD (Jacobson and Light, 2012;Light and Jacobson, 2002). Thus, the finding that six strong TIPPs are associated with measurable optical emission may not be consistent with previous findings, and thus requires examining these six events in detail.…”
Section: Using Humr As Primary Receiver: Radio-optical Temporal Relatmentioning
confidence: 77%
See 2 more Smart Citations
“…Table 4 identifies the six events and gives the time difference (median HUMR minus PDD), which is negative because the HUMR energy-weighted center time is earlier than the PDD trigger time. It has been observed in the past that dominant strong TIPPs, corresponding to the most restrictive category in produce enough light to trigger PDD (Jacobson and Light, 2012;Light and Jacobson, 2002). Thus, the finding that six strong TIPPs are associated with measurable optical emission may not be consistent with previous findings, and thus requires examining these six events in detail.…”
Section: Using Humr As Primary Receiver: Radio-optical Temporal Relatmentioning
confidence: 77%
“…2012) to emit much less light than do ordinary lightning discharges emitting strong VHF (Jacobson, 2003a;Light and Jacobson, 2002). Similarly, NBE strokes detected by a ground-based lightning-location array have not been detectable optically from space even when they were in view of an operating satellite-borne optical photometer (Jacobson and Light, 2012). These assertions are of course subject to the detection threshold of the photometer, discussed in detail elsewhere (Jacobson and Light, 2012;Kirkland et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new simple analytical model describing both bipolar and unipolar pulses was introduced by Kašpar et al, [2015]. Radio emissions associated with NBEs and other IC discharges have been detected with radio receiver on board the FORTE satellite [Light and Jacobson, 2002;Jacobson and Shao, 2002;Jacobson and Heavner, 2005;Jacobson and Light, 2012]. It was also shown that the NBE radio emission can propagate in the Earth-ionosphere waveguide and can be recorded on the ground hundreds of kilometers from the source [Smith et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed description of the project and its performance was done by, e.g. (Jacobson et al, 1999;Jacobson et al, 2000;Jacobson, 2003;Jacobson and Light, 2012). Here we would like to mention only some important features of this radio instrument.…”
Section: Introductionmentioning
confidence: 99%